Iowa RBA, January 26, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for January 26, 1998. Highlights include Snowy Owl, Varied Thrush, Glaucous Gull, Thayer's Gull, Lesser Black-backed Gull and Eurasian Collared Dove. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed